(3cJGH aj GdUdGI Ydi GdfHj Udi Gddg Ydjg hSdes - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdGTJZGd HGdUdGI Ydi GdfHj Udi Gddg Ydjg hSde TYGQ GdeSdejf agPG cJGH TQja aj GdUdGI Ydi GdfHj Udi Gddg Ydjg hSde LeYJg ef cJH TJis
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3hGZaQ dfG hGQMefG CfJ ehdGfG aGfUQfG Ydi Gdbhe GdcGaQjfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs